Susceptibility of cervical cancer to dihydroartemisinin-induced ferritinophagy-dependent ferroptosis - Shi, Hanqiang; Xiong, Lie; Yan, Guang; Du, Shuqin; Liu, Jie; Shi, Yanbo (Frontiers in Molecular Biosciences, 2023)
The clinical therapeutics of cervical cancer is limited due to the drug resistance and metastasis of tumor. As a novel target for antitumor therapy, ferroptosis is deemed to be more susceptible for those cancer cells with resistance to apoptosis and chemotherapy. Dihydroartemisinin (DHA), the primary active metabolites of artemisinin and its derivatives, has exhibited a variety of anticancer properties with low toxicity. However, the role of DHA and ferroptosis in cervical cancer remained unclear. Here, we showed that DHA could time-dependently and dose-dependently inhibit the proliferation of cervical cancer cells, which could be alleviated by the inhibitors of ferroptosis rather than apoptosis. Further investigation confirmed that DHA treatment initiated ferroptosis, as evidenced by the accumulation of reactive oxygen species (ROS), malondialdehyde (MDA) and liquid peroxidation (LPO) levels and simultaneously depletion of glutathione peroxidase 4 (GPX4) and glutathione (GSH). Moreover, nuclear receptor coactivator 4 (NCOA4)-mediated ferritinophagy was also induced by DHA leading to subsequent increases of intracellular labile iron pool (LIP), exacerbated the Fenton reaction resulting in excessive ROS production, and enhanced cervical cancer ferroptosis. Among them, we unexpectedly found that heme oxygenase-1 (HO-1) played an antioxidant role in DHA-induced cell death. In addition, the results of synergy analysis showed that the combination of DHA and doxorubicin (DOX) emerged a highly synergistic lethal effect for cervical cancer cells, which was related also to ferroptosis. Overall, our data revealed the molecular mechanisms that DHA triggered ferritinophagy-dependent ferroptosis and sensitized to DOX in cervical cancer, which may provide novel avenues for future therapy development.